2019
DOI: 10.1101/666842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative analysis reveals RNA G-Quadruplexes in UTRs are selectively constrained and enriched for functional associations

Abstract: Identifying regulatory elements in the noncoding genome is a fundamental challenge in biology. G-quadruplex (G4) sequences are abundant in untranslated regions (UTRs) of human messenger RNAs, but their functional importance remains unclear. By integrating multiple sources of genetic and genomic data, we show that putative G-quadruplex forming sequences (pG4) in 5' and 3' UTRs are selectively constrained, and enriched for cis-eQTLs and RNA-binding protein (RBP) interactions. Using over 15,000 whole-genome seque… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 55 publications
1
27
1
Order By: Relevance
“…Recent reports have demonstrated that the majority of RNA sequences that have the ability to fold into G-quadruplex structures in vitro may be generally unfolded in cells (Guo and Bartel, 2016). Still, previous reports and our data demonstrate that the G-quadruplexes must be folded in order to be efficiently bound by FMRP (Subramanian et al, 2011), and G-quadruplex sequences have been reported to be under purifying selection (Lee et al, 2019).…”
Section: Discussioncontrasting
confidence: 45%
“…Recent reports have demonstrated that the majority of RNA sequences that have the ability to fold into G-quadruplex structures in vitro may be generally unfolded in cells (Guo and Bartel, 2016). Still, previous reports and our data demonstrate that the G-quadruplexes must be folded in order to be efficiently bound by FMRP (Subramanian et al, 2011), and G-quadruplex sequences have been reported to be under purifying selection (Lee et al, 2019).…”
Section: Discussioncontrasting
confidence: 45%
“…5A and S6A) [40][41][42][43][44]. Additionally, many of the RBPs that exhibited the strongest G4-binding signal-PRPF4, GTF2F1, FAM120A, CSTF2T, and DDX6-have recently been shown to bind at putative G4 sites in mRNA UTRs [45]. However, some published G4-binding proteins such as FMR1 did not exhibit a robust signal, perhaps due to cell-type-specific variations in binding ( Fig.…”
Section: Cross-correlation Tracks Reproducibly Cluster Rbp Data Acrosmentioning
confidence: 99%
“…Recent research revealed that the G-quadruplexes in human UTRs (Untranslated Regions) are under selective pressures [58], and some coronaviruses on bats and pangolins are closely related to SARS-CoV-2. The conservation of the potential G-quadruplexes in the SARS-CoV-2 genome under selective constraints were analyzed.…”
Section: Potential G-quadruplexes Are Under Selective Constraints In mentioning
confidence: 99%